New records of Indian Nematomorpha, with the description of a new species from the genus Chordodes - Schmidt-Rhaesa, Andreas; Lalramliana, Lalramliana (Zootaxa, 2016)
Chordodes tjorvenae, a new species of horsehair worms is described from Mizoram, Northeast India. The species is distinct from all other known species by a unique combination of cuticular charatcers. In addition, the occurrence of the genus Acutogordius, particularly A. finni, is reported for the first time from India.